Postseismic gravity change after the 2006–2007 great earthquake doublet and constraints on the asthenosphere structure in the central Kuril Islands. Issue 7 (5th April 2016) - Han, Shin‐Chan; Sauber, Jeanne; Pollitz, Fred
Abstract: Large earthquakes often trigger viscoelastic adjustment for years to decades depending on the rheological properties and the nature and spatial extent of coseismic stress. The 2006 Mw 8.3 thrust and 2007 Mw 8.1 normal fault earthquakes of the central Kuril Islands resulted in significant postseismic gravity change in Gravity Recovery and Climate Experiment (GRACE) but without a discernible coseismic gravity change. The gravity increase of ~4 μGal, observed consistently from various GRACE solutions around the epicentral area during 2007–2015, is interpreted as resulting from gradual seafloor uplift by ~6 cm produced by postseismic relaxation. The GRACE data are best fit with a model of 25–35 km for the elastic thickness and ~10 18  Pa s for the Maxwell viscosity of the asthenosphere. The large measurable postseismic gravity change (greater than coseismic change) emphasizes the importance of viscoelastic relaxation in understanding tectonic deformation and fault‐locking scenarios in the Kuril subduction zone. Key Points: The viscoelastic relaxation caused gravity change larger than the coseismic change The low Maxwell viscosity of 10 18  Pa s in the asthenosphere is responsible for the gravity change The result emphasizes the importance of viscoelastic relaxation in regional tectonic deformation